Pastoral Diagnosis of Patients with Disabilities - Sim, C K. (Journal of religion in disability & rehabilitation, 1995)
This article presents the value and method of a pastoral diagnostic procedure used for people with disabilities. A spiritual assessment form for this diagnostic procedure is provided. The content includes explication of the dual benefits of pastoral diagnosis to pastors/chaplains and those whom they serve; a case study of three patients in which spiritual assessment was used in the diagnosis; an explanation of the areas and the implementation of the spiritual assessment procedure; and a conclusion that summarizes the challenges of pastoral diagnosis.